Copper‐Zinc Oxide Catalysts for Aldehyde Hydrogenation by Direct Reductive Activation of Precursors. Issue 11 (23rd August 2022) - Hiller, Max; Köhler, Klaus
Abstract: Bulk copper‐zinc oxide hydrogenation catalysts are generally prepared by calcination of co‐precipitated precursors followed by reduction. This study reports the direct reduction in hydrogen of co‐precipitated oxy/hydroxy‐carbonate precursors omitting calcination. Dried and incompletely calcined precursors are compared with calcined catalysts. The reduction reactions in hydrogen were monitored in situ by XRD and TGA‐MS. Direct activation of precursors led to higher copper dispersions and increased catalytic activity in the hydrogenation of butyraldehyde to butanol as test reaction. Abstract : Bulk copper‐zinc oxide hydrogenation catalysts prepared by direct reductive activation of dried or incompletely calcined co‐precipitated precursors show higher copper dispersions and increased catalytic activity in the hydrogenation of aldehydes compared to classically calcined Cu/Zn metal oxides.